2023
DOI: 10.1021/acs.jmedchem.3c01151
|View full text |Cite
|
Sign up to set email alerts
|

Rearmed Bifunctional Chelating Ligand for 225Ac/155Tb Precision-Guided Theranostic Radiopharmaceuticals─H4noneunpaX

Luke Wharton,
Hua Yang,
María de Guadalupe Jaraquemada-Peláez
et al.

Abstract: Superior bifunctional chelating ligands, which can sequester both α-emitting radionuclides ( 225 Ac, 213 Bi) and their diagnostic companions ( 155 Tb, 111 In), remain a formidable challenge to translating targeted alpha therapy, with complementary diagnostic imaging, to the clinic. H 4 noneupaX, a chelating ligand with an unusual diametrically opposed arrangement of pendant donor groups, has been developed to this end. H 4 noneunpaX preferentially complexes Ln 3+ and An 3+ ions, forming thermodynamically stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Notably, H 3 trica quantitatively incorporated both terbium isotopes at 10 −5 M, followed by a drop to 40% radiolabeling efficiency at 10 −6 M. The achievable molar activity with terbium reached 1 GBq/μmol, which is comparable to published chelators such as H 4 noneunpaX. 8 At room temperature, macropa fails to incorporate [ 155 Tb]Tb 3+ at any concentration. 30 In contrast, crown has been documented to quantitatively incorporate [ 161 Tb]Tb 3+ at a concentration of 10 −6 M, 31 suggesting that within the 18-crown-6 backbone, carboxylate arms might be more suitable for Tb 3+ complexation.…”
Section: Inorganicmentioning
confidence: 55%
See 1 more Smart Citation
“…Notably, H 3 trica quantitatively incorporated both terbium isotopes at 10 −5 M, followed by a drop to 40% radiolabeling efficiency at 10 −6 M. The achievable molar activity with terbium reached 1 GBq/μmol, which is comparable to published chelators such as H 4 noneunpaX. 8 At room temperature, macropa fails to incorporate [ 155 Tb]Tb 3+ at any concentration. 30 In contrast, crown has been documented to quantitatively incorporate [ 161 Tb]Tb 3+ at a concentration of 10 −6 M, 31 suggesting that within the 18-crown-6 backbone, carboxylate arms might be more suitable for Tb 3+ complexation.…”
Section: Inorganicmentioning
confidence: 55%
“…10 More recently, a new class of nonmacrocyclic chelators with enhanced inertness has emerged, incorporating bidentate picolinic acid pendant arms with a larger backbone, thereby improving their effectiveness for larger metals such as [ 225 Ac]Ac 3+ (H 4 py4pa, H 4 picoopa) and, more recently, for [ 155 Tb]Tb 3+ (H 4 noneunpaX). 8,12,13 Comba et al have extensively explored a class of chelators based on the rigid bispidine backbone−bispa 2 , bispox 2 and L 1 ; notably, these chelators, with their preorganized backbone, stably bind to therapeutic and diagnostic radioisotopes ([ 225 Ac]Ac 3+ , [ 177 Lu]-Lu 3+ and [ 111 In]In 3+ ) under mild conditions. 14−16 In the past few years, Wilson and co-workers (macropa, macrodipa, py-and py 2 -macrodipa) and Yang et al (crown), have been at the forefront of developing macrocyclic chelators with larger ring structures based on an 18-membered macrocyclic scaffold.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A pilot study involving peptides conjugated to H4noneunpaX demonstrated the effectiveness of the new chelate complex for radiopharmaceuticals targeting tumors. 40 ■ CONCLUSIONS Table 1 is an example of the presentation of important information on radiopharmaceuticals, which should be provided in publications. This simplifies the understanding of scientific findings in radiopharmaceutical science.…”
Section: Imaging and Therapymentioning
confidence: 99%
“…The radio­labeling properties of H4noneunpaX were assessed with [ 44 Sc]­Sc 3+ , [ 111 In]­In 3+ , [ 155 Tb]­Tb 3+ , [ 177 Lu]­Lu 3+ , [ 213 Bi]­Bi 3+ , and [ 225 Ac]­Ac 3+ , demonstrating quantitative radio­chemical yields (RCYs) within 10 min at ambient temperature and achieving notably high molar activities. A pilot study involving peptides conjugated to H4noneunpaX demonstrated the effectiveness of the new chelate complex for radio­pharmaceuticals targeting tumors …”
Section: Other Radiopharmaceuticals For Imagingmentioning
confidence: 99%
“…This indirect method of detection requires the assumption that 221 Fr and 213 Bi remain localized at the targeted 225 Ac decay site, which may not always be a valid assumption due to the nuclear recoil 225 Ac undergoes (de Kruijff et al 2015(de Kruijff et al , 2019. Secondly, a surrogate diagnostic radionuclide can be used to form a counterpart to an 225 (Wharton et al 2023b). This method requires the assumption that both radiopharma ceuticals have very similar or identical biodistributions and pharmacokinetics despite often having very different half-lives and chelation chemistry (Bobba et al 2023).…”
Section: Introductionmentioning
confidence: 99%